GERIATRIC ANESTHESIA: EVALUATING THE IMPACT OF AGE-RELATED PHYSIOLOGICAL CHANGES ON ANAESTHETIC PRACTICES - Edi, Reno Laksono (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Background: As the global population ages, the number of elderly patients undergoing surgical procedures increases, posing unique challenges for anesthetic management. Age-related physiological changes affect multiple organ systems, impacting the pharmacokinetics and pharmacodynamics of anesthetic agents. Understanding these changes is crucial for optimizing perioperative care in geriatric patients.Objective: This literature review aims to comprehensively evaluate the impact of age-related physiological changes on anesthetic practices and outcomes in geriatric patients. By synthesizing current research, the review seeks to provide insights into tailored approaches for anesthesia in the elderly population, encompassing hemodynamic management, ventilation strategies, drug selection and dosing, and postoperative care.Methods: A comprehensive literature search was conducted to identify studies on the impact of age-related physiological changes on aesthetic practices in geriatric patients. Electronic databases were searched using specific keywords. Inclusion criteria encompassed peer-reviewed articles focusing on anesthesia patients aged 65 and older, while exclusion criteria eliminated studies not published in English or those focusing solely on pediatric or adult populations under 65. Data extraction and synthesis involved organizing findings on cardiovascular, respiratory, renal, hepatic, and central nervous system changes, aesthetic implications, and strategies for perioperative management.Results: Age-related physiological changes significantly influence anesthetic practices in geriatric patients. These changes necessitate tailored approaches to hemodynamic management, ventilation strategies, drug selection and dosing, and postoperative care. Techniques such as regional anesthesia and multimodal analgesia mitigate risks and improve outcomes. Collaborative multidisciplinary care is essential for optimizing perioperative management in elderly patients.Conclusion: Optimizing anesthetic care in geriatric patients requires a comprehensive understanding of age-related physiological changes and their implications for perioperative management. Tailored approaches that consider these changes, utilize appropriate anesthetic techniques, and implement multidisciplinary care strategies are crucial for improving surgical outcomes and enhancing the quality of life in elderly patients. Ongoing research and education are essential for advancing geriatric anesthesia practice and addressing the evolving needs of this growing patient population.